2017
DOI: 10.1002/rcm.7817
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of uranium‐mandelic acid complexes using electrospray ionization mass spectrometry and density functional theory

Abstract: The most intense peak observed in ESI-MS, UO (MA) , was found to be the energetically most favorable amongst different UO (MA) type species. Metal-ligand equilibria studied in the two modes yielded similar results. The combined experimental and quantum chemical investigations predict that T-shape complexes may be formed even in the gas phase. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this regard, we considered a cyclic water cluster (pentamer) as the expelled moiety for the free-energy calculations (Table S1, Supporting information) . The choice of density functional for optimization (BP86) and single points (B3LYP) is based on prior investigations, which suggested that BP86 provides better structural properties (bond length, vibrational frequencies), while B3LYP is better for estimating the energetics with good accuracy. We will demonstrate that BP86-optimized structures are indeed in excellent agreement with the available crystal structures. However, to be confident about the obtained trend in Δ G bind , an additional set of calculations was performed using two other density functionals for single points (BP86 and B2PLYP). …”
Section: Experimental Sectionmentioning
confidence: 89%
“…In this regard, we considered a cyclic water cluster (pentamer) as the expelled moiety for the free-energy calculations (Table S1, Supporting information) . The choice of density functional for optimization (BP86) and single points (B3LYP) is based on prior investigations, which suggested that BP86 provides better structural properties (bond length, vibrational frequencies), while B3LYP is better for estimating the energetics with good accuracy. We will demonstrate that BP86-optimized structures are indeed in excellent agreement with the available crystal structures. However, to be confident about the obtained trend in Δ G bind , an additional set of calculations was performed using two other density functionals for single points (BP86 and B2PLYP). …”
Section: Experimental Sectionmentioning
confidence: 89%
“…The pK a of HIBA is 3.8, whereas for mandelic acid, it is 3.4. 66,67 At pH 5.0, which is slightly higher than the pK a values of both acids, both will exist predominantly in their deprotonated forms. However, as mandelic acid has a lower pK a than HIBA, it will have a higher percentage of its molecules in the deprotonated form at pH 5.0.…”
Section: Aqueous Speciation and Complexation Stabilitymentioning
confidence: 97%
“…The relative abundance of ML1 < ML2 < ML3 species in ESI-MS suggest a qualitative correlation between calculated free energies and observed complex relative stabilities. A similar approach was adopted to investigate the speciation of uraniummandelic acid complexes (Kumar et al, 2017) determining structures and free energies of the complexes that were in fair agreement with the ESI spectra. Based on the energetics of this latter study, the authors further predicted the formation of T-shaped dimeric uranyl complexes in the complexation process.…”
Section: Agmentioning
confidence: 99%